2016
DOI: 10.1111/cup.12778
|View full text |Cite
|
Sign up to set email alerts
|

Automated quantification of Ki67/MART1 stains may prevent false‐negative melanoma diagnoses

Abstract: PHH3 added limited information, but supplemental automated Ki67 assessment could possibly have prevented the misdiagnosis of most melanomas had the algorithm been available at the time of diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The proliferation marker, Ki67, has been widely used for assisting with diagnosis of melanoma 17 . The present study analyzed whether Ki67 expression was related to OS using clinicopathological data and follow-up data of the 123 patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The proliferation marker, Ki67, has been widely used for assisting with diagnosis of melanoma 17 . The present study analyzed whether Ki67 expression was related to OS using clinicopathological data and follow-up data of the 123 patients.…”
Section: Resultsmentioning
confidence: 99%
“…But there is limited information involving Ki67 expression in melanoma. The previous studies, mainly involving cutaneous melanoma, focused on the value of Ki67 expression in the differential diagnosis of benign and malignant tumors 17 . In cutaneous melanoma, the Ki67 expression index is demonstrated to correlate with tumor grade and patient survival 18 , 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, such manual counting was probably also prone to some error, as observers tire or inadequately discriminate. Increasingly, machine learning approaches are improving and becoming more accurate than manual methods in a range of disciplines (e.g., medicine, identification of melanomas [55] and astronomy, identification of chorus elements [56]). There is no reason why our approach, and more broadly, approaches of counting animals using drone imagery and machine learning, will not become increasingly more accurate and more efficient with growing amounts of data, with wide applications.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study sought to investigate whether the Ki-67 index is able to prevent false-negative diagnoses in melanomas. The authors proposed that a high cellular proliferation rate may be suggestive of melanoma and that the Ki-67 proliferation index might help prevent misdiagnoses of melanomas initially classified as benign or dysplastic nevi [25]. By comparing the prognostic impact of phosphohistone H3/MART1, Ki67/MART1, and hematoxylin and eosin staining, another study found alternatives to conventional detection of mitosis based on hematoxylin and eosin staining in the first two stages of primary cutaneous melanoma [26].…”
Section: Ki-67mentioning
confidence: 99%